Cardiorespiratory fitness: a comparison between children with renal transplantation and children with congenital solitary functioning kidney. Issue 1 (December 2016) - Lubrano, Riccardo; Tancredi, Giancarlo; Falsaperla, Raffaele; Elli, Marco
Abstract Children with end-stage renal disease are known to have a cardiorespiratory fitness significantly reduced. This is considered to be an independent index predictive of mortality mainly due to cardiovascular accidents. The effects of renal transplantation on cardiorespiratory fitness are incompletely known. We compared the maximal oxygen uptake (VO2 max) of children with a functioning renal transplant with that of children with congenital solitary functioning kidney, taking into consideration also the amount of weekly sport activity.